Genome-Wide Analysis of NBS-LRR Genes From an Early-Diverging Angiosperm Euryale ferox - Qian, Lan-Hua; Wu, Jia-Yi; Wang, Yue; Zou, Xin; Zhou, Guang-Can; Sun, Xiao-Qin (Frontiers in Genetics, 2022)
NBS-LRR genes are the largest gene family in plants conferring resistance to pathogens. At present, studies on the evolution of NBS-LRR genes in angiosperms mainly focused on monocots and eudicots, while studies on NBS-LRR genes in the basal angiosperms are limited. Euryale ferox represents an early-diverging angiosperm order, Nymphaeales, and confronts various pathogens during its lifetime, which can cause serious economic losses in terms of yield and quality. In this study, we performed a genome-wide identification and analysis of NBS-LRR genes in E. ferox. All 131 identified NBS-LRR genes could be divided into three subclasses according to different domain combinations, including 18 RNLs, 40 CNLs, and 73 TNLs. The E. ferox NBS-LRR genes are unevenly distributed on 29 chromosomes; 87 genes are clustered at 18 multigene loci, and 44 genes are singletons. Gene duplication analysis revealed that segmental duplications acted as a major mechanism for NBS-LRR gene expansions but not for RNL genes, because 18 RNL genes were scattered over 11 chromosomes without synteny loci, indicating that the expansion of RNL genes could have been caused by ectopic duplications. Ancestral gene reconciliation based on phylogenetic analysis revealed that there were at least 122 ancestral NBS-LRR lineages in the common ancestor of the three Nymphaeaceae species, suggesting that NBS-LRR genes expanded slightly during speciation in E. ferox. Transcriptome analysis showed that the majority of NBS-LRR genes were at a low level of expression without pathogen stimulation. Overall, this study characterized the profile of NBS-LRR genes in E. ferox and should serve as a valuable resource for disease resistance breeding in E. ferox.